A new species of Polypedilum Kieffer from bromeliads in Parque Nacional Cusuco, Honduras (Chironomidae: Chironominae) - Mendes, Humberto F.; Andersen, Trond; Jocqué, Merlijn (Zootaxa, 2011)
Polypedilum (P.) panacu sp. n. is described and illustrated based on all life-stages. The larva was collected from the leafaxils of the bromeliad Tillandsia guatemalensis L.B. Smith in Cusuco National Park, Honduras and reared in the laboratory. The male of the new species can be separated from the remaining Neotropical Polypedilum s. str. species by the spotted wings combined with the shape of the superior volsella and the number of setae on tergite IX; the female by the two dark spots on the anal part of the wings; the pupae on the presence of spinules on conjunctives III–IV, IV–V and V–VI and the larva on the shape of mentum and pecten epipharyngis.